Gas phase acetic acid and its qualitative effects on snow crystal morphology and the quasi-liquid layer - T. N. Knepp; T. L. Renkens; P. B. Shepson (Atmospheric Chemistry and Physics, 2009)
A chamber was constructed within which snow crystals were grown on a string at various temperatures, relative humidities, and acetic acid gas phase mole fractions. The temperature, relative humidity, and acid mole fraction were measured for the first time at the point of crystal growth. Snow crystal morphological transition temperature shifts were recorded as a function of acid mole fraction, and interpreted according to the calculated acid concentration in the crystal's quasi-liquid layer, which is believed to have increased in thickness as a function of acid mole fraction, thereby affecting the crystal's morphology consistent with the hypothesis of Kuroda and Lacmann. Deficiencies in the understanding of the quasi-liquid layer and its role in determining snow crystal morphology are briefly discussed.